2021
DOI: 10.22159/ajpcr.2021.v14i5.41355
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of an High-Performance Liquid Chromatography Method for the Determination of 17-Β Estradiol in Polymeric Nanoparticles

Abstract: Objective: A simple high-performace liquid chromatography method was developed and validated to determine 17-β estradiol in poly (ε-caprolactone) nanocapsules. Methods: The chromatographic conditions were as follows: C18 GL column with a mobile phase of acetonitrile:water (92:8 v/v) at flow rate of 1.5 mL/min with detection at 280 nm. The evaluated parameters were specificity, linearity, limits of detection and quantification, precision, accuracy, and robustness. Results: The method was specific an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Only a validated method should be employed for the estimation of drugs. The developed method was validated following the ICH Q2 (R1) guidelines and other literatures using the prescribed validation parameters [19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Methods Validationmentioning
confidence: 99%
“…Only a validated method should be employed for the estimation of drugs. The developed method was validated following the ICH Q2 (R1) guidelines and other literatures using the prescribed validation parameters [19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Methods Validationmentioning
confidence: 99%
“…The most substantial naturally-occurring human estrogen is 17 -estradiol (Figure 1) [1]. This β hormone, also known chemically as 1,3,5(10)estratrien-3,17-diol, is the most potent among endogenous estrogen steroids, including estrone and estriol.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have demonstrated that HPLC is the most feasible and accurate technique for ensuring LIS quality in terms of mass and identifying structures. [8][9][10][11][12][13] A few techniques recorded for LIS in the published literature are spectrophotometry, [14][15][16] gas-liquid chromatography, 17 capillary electrophoresis, and polarography. 18,19 By creating and validating an HPLC method for the analysis of LIS in both bulk and gel formulation, our research intends to close this gap.…”
Section: Introductionmentioning
confidence: 99%